Cytotoxic Effects of Rabbit Anti-thymocyte Globulin Preparations on Primary Human Thymic Epithelial Cells. Issue 11 (November 2019) - Kaebisch, Eva M.; Cho, Mi-Young; Oh, Young-Seong; Olfe, Lisa I.; Szyska, Martin; Becker, Sonya C.; Reinke, Petra; Volk, Hans-Dieter; Gillissen, Bernhard; Bullinger, Lars; Thiel, Andreas; Na, Il-Kang
Abstract : Background: Graft-versus-host disease (GvHD) presents a major cause for morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Rabbit-derived antithymocyte globulin (rATG) treatment reduces the incidence of GvHD after allogeneic hematopoietic stem cell transplantation. However, delayed immune reconstitution following rATG treatment, partly caused by hampered thymic function, is being discussed. The present study aims at elucidating possible cytotoxic effects of 2 commonly used rATG preparations on cultured human thymic stroma, especially thymic epithelial cells (TECs). Methods: A primary TEC culture was established and the binding and cytotoxicity of 2 rATG preparations to the aforementioned cells were assessed by flow cytometry and immunofluorescence analyses. The release of several cytokines by cultured thymic stroma cells in response to rATG was analyzed via multiplex enzyme-linked immunosorbent assays. Results: Both preparations showed a comparable dose-dependent binding to TECs and exerted a similar complement-independent, dose-dependent cytotoxicity. rATG exposure further resulted in hampered secretion of interleukin (IL)-7, IL-15, and IL-6, cytokines being involved in thymic T cell development and proliferation. Pretreatment with keratinocyte growth factor diminished rATG-induced cytotoxicity of TECs and restored their IL-7 and IL-15 secretion. Conclusions: Cytotoxic effects on TECs link the rATG-induced thymic damage to the delayed T cell reconstitution, witnessed after rATG treatment. Our data support a combination treatment of rATG and thymus-protective strategies such as keratinocyte growth factor to simultaneously offer sufficient GvHD prophylaxis and overcome delayed T cell reconstitution caused by thymic damage.